“Clearly a Subjective Determination”: Interpretations of “Undue Suffering” at the Canada Agricultural Review Tribunal (2000–2019) - Sniderman, Andrew (Ottawa Law Review / Revue de droit d’Ottawa)

(untitled) (Ottawa Law Review / Revue de droit d’Ottawa, 2021)
How much suffering does our legal system tolerate? This paper focuses on Canada’s federal Health of Animals Regulations, which purport to provide a measure of protection to farmed animals, notably during their transit to slaughterhouses. More specifically, this paper interrogates how the concept of “undue suffering” is interpreted by the Canada Agricultural Review Tribunal (CART) and Federal Court of Appeal (FCA) between 2000 and 2019. During this period, a total of 157 CART decisions applied the “undue suffering” standard with respect to provisions of the federal Health of Animals Regulations, guided in part by three significant FCA decisions. These cases allow us to conduct a longitudinal study of the standard of “undue suffering,” to see how it is interpreted and evolves over time. A core implication is that some degree of suffering was deemed reasonable, though the contours of this permissible suffering remained ambiguous. I argue that twenty years of CART cases demonstrate the shortcomings of regulations which are premised on a standard as vague as “undue suffering.”